Critical Infrastructure – Identification and Protection - Gechkova, Teodora (Research Papers, 2020)
The article considers the EU as a region, part of which also is Bulgaria. It analyzes the critical infrastructure in the US and Canada. In the research has been suggested a procedure for identifying the national critical infrastructure, similar to the method of Czech Republic. The article has been proposed main measures for the protection of national critical infrastructure and analyzed major definitions like: risk, threat; Critical Infrastructure; European Critical Infrastructure, etc.